Konfigurasi Lanskap dan Efisiensi Energi Selubung Bangunan untuk Mitigasi Pulau Panas Perkotaan di Kota Bima - Mas'uddin; Karlinasari, Lina; Pertiwi, Setyo; Erizal (Jurnal Lanskap Indonesia, 2026)
Urban Heat Island (UHI) due to climate change, land cover configurations that tend to vary in urban landscape composition affect the Land Surface Temperature (LST) and spatial arrangement of landscape character types. Increased energy consumption of buildings. UHI intensity is one of the key variables to predict future urban energy demand. Therefore, this study aims to examine changes in the configuration of land cover landscapes to increase the LST and UHI thresholds based on spatial temporal conditions in the Bima City area for the 2021-2023 period; and evaluate the performance of solar heat transfer on the wall sheathing material of residential buildings in Bima City. This study examines the effects of land cover change on UHI and LST in Bima City from 2021-2023. Using Landsat 8 OLI /TIR data, the LST analysis showed an increase in UHI, with the highest LSI at 39 °C in 2022 and the UHI area reaching 4,028 ha. The UHI threshold value also increased, indicating the intensification of this phenomenon. Next, the study evaluated heat transfer on the walls of the house. Overall Thermal Transfer Value (OTTV) analysis according to SNI 03-6389-2020 shows that houses with red brick walls, insulation, and certain glass (R2) meet the OTTV standard of 32.14 Watt/m2. Meanwhile, houses with a dominance of glass material (R1) exceeded the standard with 35.17 Watt/m2. The conductivity of red brick and the radiation penetration of glass significantly affect heat transfer. The Window-to-Wall Ratio and the type of glass play an important role. As a result, R2, with a better material, successfully mitigates the effects of UHI compared to R1. This study highlights the importance of building material selection in reducing the impact of UHI in urban landscapes.